AZAS ULTIMUM REMEDIUM ATAUKAH AZAS PRIMUM REMEDIUM YANG DIANUT DALAM PENEGAKAN HUKUM PIDANA PADA TINDAK PIDANA LINGKUNGAN HIDUP PADA UU NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP - Kukuh Subyakto (Jurnal Pembaharuan Hukum, 2015)
Criminal law enforcement in cracking down on the provisions of environmental protection and environmental protection law (Law No. 32 of 2009) is not the only means of enforcing environmental law. In addition to criminal sanctions stipulated in Law no. 32 of 2009 on UUPPLH there are still other sanctions for individuals and corporations that violate the provisions in the protection and management of the environment.The principle of ultimum remedium is the principle of criminal law, in which criminal punishment or punishment is an alternative or last resort in law enforcement including law enforcement in the field of living environment, while primum remedium is the opposite of ultimum remedium where criminal law enforcement through criminal sanction in the form of imposition of suffering against a person As well as corporations are preferred in law enforcement including enforcement of environmental law.Law No. 32 of 2009 on Environmental Protection and Management in enforcing its criminal provisions emphasizes the application of premature remedium principles in enforcingenvironmental criminal law.